Enhancing crop growth in rooftop farms by repurposing CO2 from human respiration inside buildings - Buckley, Sarabeth; Sparks, Rebecca; Cowdery, Elizabeth; Stirling, Finn; Marsching, Jane; Phillips, Nathan (Frontiers in Sustainable Food Systems, 2022)
Integrating cities with the surrounding environment by incorporating green spaces in creative ways would help counter climate change. We propose a rooftop farm system called BIG GRO where air enriched with carbon dioxide (CO2) through respiration from indoor spaces is applied through existing ventilation systems to produce a fertilization effect and increasing plant growth. CO2 measurements were taken inside 20 classrooms and at two exhaust vents on a rooftop at Boston University in Boston, MA. Exhausted air was directed toward spinach and corn and the biomass and leaf number were measured. High concentrations of CO2 persisted inside classrooms and at rooftop exhaust vents in correlation with expected human occupancy. CO2 levels averaged 1070 and 830 parts per million (ppm), reaching a maximum of 4470 and 1300 ppm CO2 indoors and at exhaust vents, respectively. The biomass of spinach grown next to exhaust air increased 4-fold compared to plants grown next to a control fan applying atmospheric air. High wind speed decreased growth by approximately 2-fold. The biomass of corn, a C4 plant, experienced a 2- to 3-fold increase, indicating that alternative environmental factors, such as temperature, could contribute to growth enhancement. Enhancing growth in rooftop farms using indoor air would help increase yield and help crops survive harsh conditions, which would make their installation in cities more feasible.